Transformational Leadership in Enhancing the Performance of Generation Z Employees - Pratama, Rizky Adi; Lestari, Nadya Puspita (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
The motivation behind this research is the growing influence of Generation Z in the labor force, which requires leadership styles that are more flexible, inspiring, and focused on individual development. Among these, transformational leadership is the most relevant, as it fosters internal motivation and employee participation, leading to better performance. The purpose of this research is to examine the impact of transformational leadership on the performance of Generation Z workers. A quantitative method with an explanatory research design was used in a survey of 128 Generation Z employees selected through purposive sampling. The data were gathered using a Likert-scale questionnaire and processed using simple linear regression. The results reveal that transformational leadership not only positively but also significantly impacts the performance of Gen Z employees and accounts for a considerable portion of the variance in work quality, work quantity, punctuality, and responsibility. The innovation of this research lies in combining a generational view with non-monetary performance measurement in management accounting. The theoretical contributions to leadership studies and practical recommendations for companies on developing effective, long-lasting leadership strategies are the twofold benefits of this study.